Artificial intelligence and competency-based education: A bibliometric analysis - Cătălina Radu; Carmen Nadia Ciocoiu; Cristina Veith; Răzvan Cătălin Dobrea (Amfiteatru Economic, 2024)
In the context of the educational transition toward a competency-based approach, this study aimed to identify trends, challenges, and emerging opportunities generated by the intersection of Artificial Intelligence (AI) and Competency-Based Education (CBE). The research was carried out using a bibliometric analysis of 1,028 articles included in the Web of Science database and based on reports provided by the biblioshiny application, the graphical interface of the bibliometrix R package. The results included a quantitative analysis of scientific production, collaborations, and cocitations, as well as the evolution and thematic map of the field. These revealed an annual increase of 8.43% in publications with acceleration after 2017 and global involvement, with the United States and China in leading positions. Thematic analyses have shown the field's evolution from technological foundations to an interdisciplinary approach, highlighting the influences of global events, such as COVID-19. The research confirmed the profound interaction between AI and CBE, demonstrating its potential, complexity, and the need for collaborative and interdisciplinary approaches. The bibliometric analysis performed can serve as a guide for future research directions and for identifying strategic directions in the implementation of AI in education.
Keywords: I20; I21; 330; artificial intelligence (AI); competency-based education (CBE); bibliometric analysis; thematic map; Web of Science (WoS)